2023
DOI: 10.3389/phrs.2023.1605189
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Student Wellbeing Through Social Prescribing: A Rapid Realist Review

Abstract: Objectives: A Rapid Realist Review of social prescribing in Higher Education (HE) was undertaken to determine what works, for whom, how, why, and within what circumstances. The review resulted in the development of a Realist Programme Theory articulating the way in which social prescribing can be implemented within the HE environment.Methods: Searches of 12 electronic databases were supplemented by citation chaining and grey literature surfaced by the Project Advisory Group. The RAMESES Quality Standards for R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…A preliminary search of PROSPERO, MEDLINE (Ovid), JBI EBP Database (Ovid), Cochrane Library, Google, and Google Scholar was conducted on April 12, 2023. Only one underway evidence review on social prescribing and students was found [ 8 ], which is narrowly focused on enhancing student wellbeing through social prescribing. Notably, no evidence reviews with an aim to understand the extent and type of evidence on social prescribing and students were found.…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary search of PROSPERO, MEDLINE (Ovid), JBI EBP Database (Ovid), Cochrane Library, Google, and Google Scholar was conducted on April 12, 2023. Only one underway evidence review on social prescribing and students was found [ 8 ], which is narrowly focused on enhancing student wellbeing through social prescribing. Notably, no evidence reviews with an aim to understand the extent and type of evidence on social prescribing and students were found.…”
Section: Introductionmentioning
confidence: 99%